PERANCANGAN PROTOTYPE ALAT PENDETEKSI KEBOCORAN GAS LPG BERBASIS ARDUINO UNO R3 DENGAN MODUL SIM800L DAN ESP8266 SEBAGAI MEDIA INFORMASI - afdal eka kurniawan; Mayda Waruni Kasrani; a asni b (Lembaga Penelitian Universitas Balikpapan, 2020)
Abstract— The LPG (Liquefied Petroleum Gas) gas leak detection and monitoring system is an anticipatory measure for safety from hazards such as gas cylinder explosions. This research aims to build a detection system by integrating MQ-6 sensor, Arduino microcontroller and ESP8266. Data can then be displayed on the Blynk application and notifications will be given via the application and email. The process of sending data using SIM800L module GSM/GPRS is a part that serves to communicate between the main monitors with mobile phone and the module ESP8266E ESP 12E WIFI IOT for data transfer in WIFI network . And this system has fulfilled the rules of the Internet of things, making it easier for the community in its application.